SDF-1 and MMP2 cross talk in cancer cells and tumor microenvironment in non-small cell lung - Nehad M. Osman; Wesam M. Osman (Egyptian Journal of Chest Disease and Tuberculosis, 2016)
Lung cancer is the cancer killer among men and women worldwide. Attempts have been undertaken to identify potential biomarkers for lung cancer; some of which have a direct impact on tumor behavior. The association between MMPs and SDF-1 was previously studied in other organs yet the current study is conducted to evaluate their immunohistochemical expression in non-small lung cancer (NSCLC) aiming to discover their association with different clinicopathological prognostic parameters. Materials and methods: Bronchoscopy and/or C-T guided biopsy from 72 specimens of NSCLC (27 adenocarcinomas, 23 squamous cell carcinomas, and 12 large cell carcinomas) were immunohistochemically stained with MMPs and SDF-1. Results: Cytoplasmic and stromal expression of MMP-2 was seen in 39 (54.2%) patients. Nuclear SDF-1 staining was observed in 36 cases (50%). High expression of MMP-2 was correlated with tumor size (P = 0.002), lymph node (P = 0.001) and distant metastasis (P = 0.026). Nuclear SDF-1 expression was correlated with the tumor size (P = 0.001) and increased risk of metastasis (P = 0.001). A strong agreement between both markers was detected. Combined expression of MMP-2 and SDF-1 was significantly correlated with high tumor stage. MMP2 and nuclear SDF-1 were significantly independent factors in predicting high tumor stage (III and IV). Conclusion: SDF-1a directed invasion of NSCLC is mediated by crosstalk with MMP-2. The identification of SDF-1a from NSCLC tissues as a potential stimulatory factor of MMP-2 during cancer cell invasion may be involved in aggressiveness of NSCLC. Hence, identification of SDF-1a/MMP-2 interaction may implicate therapeutic approaches for metastasis from lung cancer.